Small animal ophthalmic atlas and guide - Lim, Christine C. (Ames, Iowa : Wiley Blackwell, 2015)
"Small Animal Ophthalmic Atlas and Guide offers fast access to a picture-matching guide to common ophthalmic conditions and key points related to diagnosing and managing these diseases. The first half of the book presents photographs of ophthalmic abnormalities with brief descriptions, as an aid for diagnosis. The second half of the book is devoted to concise, clinically oriented descriptions of disease processes, diagnostic tests, and treatments for each condition. Small Animal Ophthalmic Atlas and Guide is a useful tool for quickly and accurately formulating a diagnosis, diagnostic strategy, and treatment plan for small animal patients. Ideally suited for use in the fast-paced practice setting, this text provides both reference images and information for managing the disease in a single text. Small Animal Ophthalmic Atlas and Guide is an easy-to-use aid for small animal general practitioners, veterinary students, and veterinary interns seeking a quick yet complete guide to small animal ophthalmology"--Publisher's description.
Part I: Atlas. Orbit -- Eyelids -- Third eyelid, nasolacrimal system, and precorneal tear film -- Conjunctiva -- Cornea -- Anterior uvea -- Lens -- Posterior segment -- Glaucoma (page 57) -- Part II: Guide. Orbit -- Eyelids -- The third eyelid, nasolacrimal system, and precorneal tear film -- Conjunctiva -- Cornea -- Anterior uvea -- Lens -- Posterior segment -- Glaucoma.
Includes bibliographical references and index.
Description based on online resource; title from resource home page (Wiley Online Library viewed December 14, 2016).
Keywords: Veterinary ophthalmology -- Atlases; Eye -- Diseases -- Treatment -- Atlases; Eye Diseases; Animals, Domestic; MEDICAL -- Veterinary Medicine -- Small Animal; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Eye -- Diseases -- Treatment; Veterinary ophthalmology; Atlases; Atlases; Electronic books